Metodologi Pengembangan Ilmu Pendidikan Islam Prespektif Al-Qur’an Surat Fushilat ayat 53 - Fahim Tharaba (IAIN Ponorogo, 2019)
Abstrak: Islamic Education as an important scientific building to always be developed so that there is improvement in the concept and practical level. In this paper the science of Islamic education will be seen from the perspective of the letter Fushilat 53 to develop its theoretical concepts. For this reason, the contents of the Islamic education curriculum can be seen in three orientations, namely the development of science oriented on: (1) The concept of divinity (Divine). (2) The concept of humanity (anfusion) (3) The concept of experience (afaqi). Furthermore, the approach to presenting an Islamic education curriculum can be formulated as follows: (1) the level of basic education is based on a psychological-religious approach; (2) secondary education levels (first and top) are based on scientific psychological approaches; and (3) higher education levels are based on religious-scientific and philosophical approaches. So that all the development of knowledge in Islamic Education based on and based on the main and main sources of the Qur’an and as-Sunnah, and in its implementation always cannot be separated from its history. In this discussion, the main objective was to find the methodology of the development of the Islamic education in the perspective of the Al-Qur’an Surat Fushilatayat 53. ملخّص: التربية الإسلامية كمبنى علمي هام يتم تطويره باستمرار حتى يكون هناك تحسن في المفهوم والمستوى العملي. في هذا البحث سيتم النظر إلى علم التربية الإسلامية من منظور الحرف فصلت : 53 تطوير مفاهيمه النظرية. لهذا) السبب ، يمكن رؤية محتويات منهج التربية الإسلامية في ثلاثة اتجاهات ، وهي تطوير العلوم الموجهة نحو: ) 1مفهوم الألوهية ) 2( مفهوم الإنسانية ) 3( مفهوم الخبرة . علاوة على ذلك ، يمكن صياغة نهج تقديم منهج التربية الإسلامية على النحو التالي: ) 1( يعتمد مستوى التعليم الأساسي على النهج النفسي الديني ؛ ) 2( تستند مستويات التعليم الثانوي )الأول والأعلى( إلى المقاربات النفسية العلمية ؛ و ) 3( تستند مستويات التعليم العالي على المناهج الدينية والعلمية والفلسفية. بحيث لا يمكن فصل كل تطور المعرفة في التربية الإسلامية المبني على أساس المصادر الرئيسية والرائدة للقرآن والسنة ، وعلى تنفيذه على الدوام عن تاريخه. في هذه المناقشة ، كان الهدف الرئيسي هو العثور على منهجية تطوير التربية الإسلامية في منظور القرآن الكريم سورة فصلت :53